Intrant ELISA: A Novel Approach to Fabrication of Electrospun Fiber Mat-Assisted Biosensor Platforms and Their Integration within Standard Analytical Well Plates - Hosseini, S.; Azari, P.; Aeinehvand, M.M.; Rothan, H.A.; Djordjevic, I.; Martinez-Chapa, S.O.; Madou, M.J. (MDPI, 2016)
A combination of far-field electrospinning (FFES) and free-radical polymerization has been used to fabricate coated electrospun polymer fiber mats as a new type of biosensor platform. Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) electrospun fibers were dip-coated with different compositions of poly methyl methacrylate-co-methacrylic acid (poly(MMA-co-MAA)). This synergistic approach utilizes large specific surface area of PHBV fibers and co-polymer coatings that feature an optimum concentration of surface carboxyl (–COOH) groups. The platform surface morphology, porosity and tunable hydrophobicity enhance biomolecular interactions via plurality of molecular forces. These customized fiber mats have been integrated into a newly designed 96-well plate called an “intrant enzyme-linked immunosorbent assay” or i-ELISA. I-ELISA allows colorimetric sandwich assay to be carried out without any modifications or additional steps in ELISA methodology. By introducing the fiber mats in fabrication of i-ELISA via extensions on the lid, we address some of the limitations of the previous designs while demonstrating an enhanced signal intensity up to 12 times higher than that of conventional assays. With improved sensitivity, specificity and accuracy in the detection of dengue virus, i-ELISA has proven to be a reliable platform for biomolecular recognition. The proposed fiber mat-assisted well plate in this study holds great potential as a universal approach for integration of different types of fiber mats with pre-designed specific properties in order to enhance the detection sensitivity of the assay.